Low cost ionic liquid–water mixtures for effective extraction of carbohydrate and lipid from algae. (22nd September 2017) - To, Trang Q.; Procter, Kerryn; Simmons, Blake A.; Subashchandrabose, Suresh; Atkin, Rob
Abstract : Here we show that biomass derived from Chlorella vulgaris and Spirulina platensis can be pretreated with low cost choline amino acid based ionic liquids to effectively yield lipids and sugars. Abstract : Biomass based biofuels are already an important energy source, and will increasingly be so in the future as the need for renewable energy rises. Due to their fast multiplication rates, algae can provide a sustainable supply of biomass, and are attractive because they do not compete with food crops for habitat. Here we show that biomass derived from Chlorella vulgaris and Spirulina platensis can be pretreated with low cost choline amino acid based ionic liquids to effectively yield lipids (30.6% and 51% total lipids) and sugars (71% and 26% total sugars). The ionic liquids dissolve the lipids, leaving behind a carbohydrate rich solid. The lipids were extracted with hexane, and the solid was subjected to enzyme hydrolysis to release fermentable sugars. These results open new pathways towards the dual production of biodiesel and bioethanol from algae, using low cost ionic liquids.